Transcriptome profiling of sulfate deprivation responses in two agarophytes Gracilaria changii and Gracilaria salicornia (Rhodophyta) - Lee, Wei Kang; Namasivayam, Parameswari; Abdullah, Janna Ong; Ho, Chai Ling (Nature Publishing Group, 2017)
Seaweeds survive in marine waters with high sulfate concentration compared to those living at freshwater habitats. The cell wall polymer of Gracilaria spp. which supplies more than 50% of the world agar is heavily sulfated. Since sulfation reduces the agar quality, it is interesting to investigate the effects of sulfate deprivation on the sulfate contents of seaweed and agar, as well as the metabolic pathways of these seaweeds. In this study, two agarophytes G. changii and G. salicornia were treated under sulfate deprivation for 5 days. The sulfate contents in the seaweed/agar were generally lower in sulfate-deprivated samples compared to those in the controls, but the differences were only statistically significant for seaweed sample of G. changii and agar sample of G. salicornia. RNA sequencing (RNA-Seq) of sulfate-deprivated and untreated seaweed samples revealed 1,292 and 3,439 differentially expressed genes (DEGs; ≥1.5-fold) in sulfate-deprivated G. changii and G. salicornia, respectively, compared to their respective controls. Among the annotated DEGs were genes involved in putative agar biosynthesis, sulfur metabolism, metabolism of sulfur-containing amino acids, carbon metabolism and oxidative stress. These findings shed light on the sulfate deprivation responses in agarophytes and help to identify candidate genes involved in agar biosynthesis.